2011
DOI: 10.1016/j.jesp.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of immigrant acculturation preferences and generational status in determining majority intergroup attitudes

Abstract: Two experiments (Ns = 220, 135) investigated the role of first and second generation immigrants' desire for Culture Maintenance and Intercultural Contact in affecting majority members' intergroup attitudes (2 × 2 × 2 design). Participants were presented with fictitious interviews through which immigrants' acculturation preferences and generational status were manipulated. Immigrants' desire for contact strongly affected host members' attitudes: those who were perceived to want contact elicited more favourable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 45 publications
12
63
1
2
Order By: Relevance
“…Moreover, the findings support the approach of measuring the dimensions of acculturation separately (Matera et al, 2011), as contact and culture maintenance gave rise to different intergroup climates for Christian and Muslim immigrants. following depictions of high versus low levels of minorities' identification with their heritage culture (Van Oudenhoven et al, 2006).…”
Section: Limitations and Perspectives For Future Researchsupporting
confidence: 66%
See 3 more Smart Citations
“…Moreover, the findings support the approach of measuring the dimensions of acculturation separately (Matera et al, 2011), as contact and culture maintenance gave rise to different intergroup climates for Christian and Muslim immigrants. following depictions of high versus low levels of minorities' identification with their heritage culture (Van Oudenhoven et al, 2006).…”
Section: Limitations and Perspectives For Future Researchsupporting
confidence: 66%
“…In line with H1, the results revealed that when minority members were perceived to desire contact, it generated positive intergroup attitudes among members of the majority. In addition to this, when both minorities sought contact, majority members reported lower levels of threat (H2) (Celeste et al, 2014;Matera et al, 2011). Majority members also associated both the Christian and Muslim minority who wished to maintain their culture with increased threat.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dans les trois écoles où notre étude a été menée, la volonté de s'intégrer aux élèves d'origine québécoise et de devenir amis avec eux était l'un des plus importants résultats émergeant des données provenant des entrevues avec des élèves issus de l'immigration (Steinbach et Lussier, 2013). Selon Matera, Stefanile et Brown (2011), le désir pour le contact intergroupe chez les immigrants susciterait des attitudes positives de la part des membres de la société d'accueil et réduirait la perception de menace et les métastéréotypes négatifs. Toutefois, dans les écoles A et B, il semble que ce désir n'était pas perçu des élèves d'origine québécoise, qui parlaient plutôt de conflits et qui ne voyaient pas ou peu les efforts faits par les nouveaux arrivants.…”
Section: Discussionunclassified